Determination of acetylcysteine and cysteine in pharmaceutical formulations using a smartphone-based digital image colorimetric method - Sahin, Nurulhuda; Kustanto, Tulay Borahan; Zaman, Buse Tugba; Korkunc, Ummugulsum Polat; Gel, Mehmet Selim; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2024)
A digital image colorimetry method utilizing a smartphone as the detection tool was developed for the determination of acetylcysteine and cysteine in effervescent tablets. The method is based on a simple nitroprusside test specific for free -SH groups in aminothiols, which results in orange-red color sample solutions for colorimetric detection. The analytical response of the colorimetric detection decreased as the amino acid concentration increased. The data of the digital images taken were processed to RGB (red-green-blue) color scales using the Color Detector application. Today's technology allows faster and easier analysis with the use of easily accessible and portable smartphones in colorimetric detection systems. The developed method has good linearity in a linear working range of 5.0-25 mg/L (41.27-206.34 mu M) and 4.94-47.30 mg/kg (30.27-289.85 mu M) for cysteine and acetylcysteine, respectively. The limit of detection and quantification values for cysteine and acetylcysteine were calculated as 1.0 and 3.4 mg/L (8.25-28.06 mu M) and 1.8 and 6.1 mg/kg (11.03-37.38 mu M), respectively. The applicability and accuracy of the developed method were tested on drug samples. According to the results, this method has the potential to be used in the routine analysis and quality control of pharmaceutical formulations.
Keywords: Aminothiols; Acetylcysteine; Cysteine; Nitroprusside test; Smartphone; Digital image; Colorimetry; PERFORMANCE LIQUID-CHROMATOGRAPHY; PEROXIDASE-LIKE ACTIVITY; AMINO-ACIDS; HUMAN PLASMA; BIOMARKERS; HPLC; NANOPARTICLES; HOMOCYSTEINE; NONCONTACT; Chemistry